ADDITION OF UNSYMMETRICAL DIENES TO ACYL-1,4-BENZOQUINONES AND OXIDATION OF THE ADDUCTS WITH MANGANESE DIOXIDE: A REGIOSPECIFIC ROUTE TO MONO- AND DI-METHYL-1,4-NAPHTHOQUINONES (Journal of Sciences, Islamic Republic of Iran)
Regioselective Diels-Alder reactions of acyl-1,4-benzoquinones 1 with, severally, isoprene, trans-piperylene,1-acetoxy-1,3-butadiene and 1-methoxy-1,3-butadiene gave the corresponding adducts 2 in high yield. Treatment of the adducts 2 with manganese dioxide gave regiospecifically the corresponding 1,4-naphthoquinones 3. In several cases, the adducts of the acetylquinones afforded intermediates of type 4, which subsequently gave the corresponding naphthoquinones by de-acetylation and aromatization.